Brief Report: Cutaneous Melanoma Risk Among People With HIV in the United States and Canada. (15th August 2018) - Yanik, Elizabeth L.; Hernández-Ramírez, Raúl U.; Qin, Li; Lin, Haiqun; Leyden, Wendy; Neugebauer, Romain S.; Horberg, Michael A.; Moore, Richard D.; Mathews, W. Christopher; Justice, Amy C.; Hessol, Nancy A.; Mayor, Angel M.; et al.
Abstract : Background: Cutaneous melanoma incidence may be modestly elevated in people with HIV (PWH) vs. people without HIV. However, little is known about the relationship of immunosuppression, HIV replication, and antiretroviral therapy (ART) with melanoma risk. Methods: PWH of white race in the North American AIDS Cohort Collaboration on Research and Design were included. A standardized incidence ratio was calculated comparing risk with the white general population, standardizing by age, sex, and calendar period. Associations between melanoma incidence and current, lagged, and cumulative measures of CD4 count, HIV RNA level, and ART use were estimated with Cox regression, adjusting for established risk factors such as age and annual residential ultraviolet B (UVB) exposure. Results: Eighty melanomas were diagnosed among 33, 934 white PWH (incidence = 40.75 per 100, 000 person-years). Incidence was not elevated compared with the general population [standardized incidence ratio = 1.15, 95% confidence interval (95% CI) = 0.91 to 1.43]. Higher melanoma incidence was associated with older age [adjusted hazard ratio (aHR) per decade increase = 1.50, 95% CI = 1.20 to 1.89] and higher UVB exposure (aHR for exposure ≥35 vs. <35 mW/m 2 = 1.62, 95% CI = 0.99 to 2.65). Current, lagged, and cumulative CD4 and HIV RNA were not associated with melanoma incidence. Melanoma incidence was higher among people ART-treated for a larger proportion of time in the previous 720 days (aHR per 10% increase = 1.16, 95% CI = 1.03 to 1.30). Conclusions: These results suggest that HIV-induced immune dysfunction does not influence melanoma development. The association between ART and melanoma risk may be due to increased skin surveillance among PWH engaged in clinical care. Associations with age and UVB confirmed those established in the general population.